Sustained Energy Deficit Following Perinatal Asphyxia: A Shift towards the Fructose-2,6-bisphosphatase (TIGAR)-Dependent Pentose Phosphate Pathway and Postnatal Development - Carolyne Lespay-Rebolledo; Andrea Tapia-Bustos; Ronald Perez-Lobos; Valentina Vio; Emmanuel Casanova-Ortiz; Nancy Farfan-Troncoso; Marta Zamorano-Cataldo; Martina Redel-Villarroel; Fernando Ezquer; Maria Elena Quintanilla; Yedy Israel; Paola Morales; et al. (MDPI AG, 2021)
Labor and delivery entail a complex and sequential metabolic and physiologic cascade, culminating in most circumstances in successful childbirth, although delivery can be a risky episode if oxygen supply is interrupted, resulting in perinatal asphyxia (PA). PA causes an energy failure, leading to cell dysfunction and death if re-oxygenation is not promptly restored. PA is associated with long-term effects, challenging the ability of the brain to cope with stressors occurring along with life. We review here relevant targets responsible for metabolic cascades linked to neurodevelopmental impairments, that we have identified with a model of global PA in rats. Severe PA induces a sustained effect on redox homeostasis, increasing oxidative stress, decreasing metabolic and tissue antioxidant capacity in vulnerable brain regions, which remains weeks after the insult. Catalase activity is decreased in mesencephalon and hippocampus from PA-exposed (AS), compared to control neonates (CS), in parallel with increased cleaved caspase-3 levels, associated with decreased glutathione reductase and glutathione peroxidase activity, a shift towards the TIGAR-dependent pentose phosphate pathway, and delayed calpain-dependent cell death. The brain damage continues long after the re-oxygenation period, extending for weeks after PA, affecting neurons and glial cells, including myelination in grey and white matter. The resulting vulnerability was investigated with organotypic cultures built from AS and CS rat newborns, showing that substantia nigra TH-dopamine-positive cells from AS were more vulnerable to 1 mM of H2O2 than those from CS animals. Several therapeutic strategies are discussed, including hypothermia; N-acetylcysteine; memantine; nicotinamide, and intranasally administered mesenchymal stem cell secretomes, promising clinical translation.